Penggunaan Modifikasi dan Promosi Produk Pada Pengusaha Catering di Kecamatan Antapani Kota Bandung - Sadikin, Taufik; Bramasto, Ari; Anggadini, Sri Dewi (Jurnal Pengabdian Tri Bhakti, 2022)
Srirahayu catering is located in Antapani Kulon, Kec. Antapani, Bandung City, West Java. The location of the business being carried out is a strategic area, located near the market which ultimately makes it easier for business owners to obtain raw materials, in terms of marketing this area is close to transportation facilities as well as easy access to the main road. The preliminary survey conducted found several problems that occurred in Srirahayu catering include the lack of knowledge of product modification, difficulties in carrying out promotions, limited product marketing problems. We hope that the community service program that we run is able to socialize the use of cardboard food packaging and help partners promote their products through social media